Programming with Objects: A Comparative Presentation of Object-Oriented Programming with C++ and Java - Kak, Avinash C. (John Wiley & Sons, 2011)
This resource is designed as a text for educational programs in advanced programming and as a reference for professionals implementing Web- and Internet-based applications.